DRAGON FRUIT (Hylocereus polyrhizus) AS NATURAL DYES STAINING FOR BACTERIA - Yunan Jiwintarum; Rohmi Rohmi; I Dewa Putu Martha Prayuda (Jurnal Kesehatan Prima, 2016)
Abstract :  the bacteria is difficult to be perceived with a light microscope because it can not adsorb or refract the light, consequently the dye applies for staining the bacteria or their background. Synthetic dye has a fairly expensive price than natural dye. This study aims to determine the usage of dragon fruit (Hylocereus polyrhizus) as a natural dye for staining the bacteria. This research is quasi experimental, while the data will be analysed by descriptive analysis with 3 treatments, in each uses eight samples. The study showed that on the quality of stains, bacterium Staphylococcus aureus and E. coli by using the juice of the dragon is obtained a result, as many as 4 slides preparations of bacteria Staphylococcus aureus (33.33%) and 4 slides preparations of bacteria E .coli (33.33%) were not stained. Therefore, the result on the research can be concluded that the dragon fruit (Hylocereus polyrhizus) can not be used as a natural dye for staining bacteria.